Pengaruh Loan To Deposit Ratio , Non-Performing Loan, dan Net Interest Margin Terhadap Profitabilitas Bank Swasta Devisa Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - Riza Dian Cahyani; Bayu Kurniawan; Heri Prabowo (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Banking is a vital sector in the economy of a country, including Indonesia. National Private Foreign Exchange Banks play a crucial role in providing financial services related to foreign currencies. In this context, factors such as Loan to Deposit Ratio, Non-Performing Loans, and Net Interest Margin are pivotal in determining the profitability of banks. This research aims to analyze the influence of Loan to Deposit Ratio, Non-Performing Loans, and Net Interest Margin on the profitability of National Private Foreign Exchange Banks listed on the Indonesia Stock Exchange during the period 2018-2022. The study employs a quantitative approach with secondary data collection from the financial reports of National Private Foreign Exchange Banks listed on the Indonesia Stock Exchange. Data analysis technique utilizes panel data regression to examine the effects of Loan to Deposit Ratio, Non-Performing Loans, and Net Interest Margin variables on bank profitability. The research findings indicate that Non-Performing Loans and Net Interest Margin significantly affect the profitability of National Private Foreign Exchange Banks, whereas Loan to Deposit Ratio does not exert a significant influence. These variables exhibit a complex relationship in influencing the financial performance of banks. From these research findings, it is concluded that the management of Loan to Deposit Ratio needs improvement, accompanied by considerations of Non-Performing Loans and Net Interest Margin factors, to enhance the profitability of National Private Foreign Exchange Banks.